Improvising the six row manually operated paddy seedling transplanter through value engineering. (6th November 2019) - Mohan, M.; Sundararaj, G.; Devadasan, S.R.; Murugesh, R.
In this paper, a research in which value engineering principles were applied to improvise a six row manually operated paddy transplanter has been reported. While pursuing this research, the classical approach called 'value engineering job plan' was followed. By following this approach, the value of six row manually operated paddy transplanter was enhanced by carrying out the activities systematically and scientifically in eight phases by using appropriate tools. On executing these phases, the cost and weight of the parts involved in manufacturing the six row manually operated paddy transplanter were reduced by 38.79 percentage and 39.93 percentage respectively. Furthermore, eight components have been removed in the newly improvised six row manually operated paddy transplanter. The outcomes of the research reported in this paper have revealed that the application of value engineering job plan has facilitated to enhance the value of the six row manually operated paddy transplanter.